2019
DOI: 10.1007/s11065-019-09411-w
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological and Cognitive Profile of Young Binge Drinkers: a Systematic Review and Meta-Analysis

Abstract: This review provides the first systematic and quantitative synthesis of the literature examining the relationship between binge drinking, cognition, brain structure and function in youth aged 10 to 24 years. PubMed, EMBASE, Medline, PsychINFO and ProQuest were searched for neuroimaging, neurophysiological, and neuropsychological studies. A total of 58 studies (21 neuroimaging, 16 neurophysiological, 21 neuropsychological) met the eligibility criteria and were included in the review. Overall, abnormal or delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 134 publications
2
63
0
3
Order By: Relevance
“…Reward hypersensitivity in combination with low inhibition is thought to increase adolescents' drive for risky and novel experiences, such as alcohol use (30,32). Neurotoxin exposure, particularly alcohol use, during adolescence can affect healthy brain development, with even minor changes in neurodevelopmental trajectories affecting a range of cognitive, emotional, and social functioning (4). Alcohol use during adolescence could therefore set the stage for cognitive problems into adulthood, conferring functional consequences throughout life.…”
Section: Overview Of the Adolescent Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Reward hypersensitivity in combination with low inhibition is thought to increase adolescents' drive for risky and novel experiences, such as alcohol use (30,32). Neurotoxin exposure, particularly alcohol use, during adolescence can affect healthy brain development, with even minor changes in neurodevelopmental trajectories affecting a range of cognitive, emotional, and social functioning (4). Alcohol use during adolescence could therefore set the stage for cognitive problems into adulthood, conferring functional consequences throughout life.…”
Section: Overview Of the Adolescent Brainmentioning
confidence: 99%
“…Notably, alcohol use behaviors at ages 12 to 14 predict lower educational achievement in later years, even after accounting for confounding factors such as sex and externalizing behavior (51). A recent meta-analysis of cross-sectional studies reported adolescent binge drinking was associated with an overall cognitive deficit and specific impairments in decision-making and inhibition (4). Herein, we report on longitudinal studies that have identified potential negative effects of adolescent binge drinking and heavy alcohol use on memory, learning, visuospatial function, executive function, reading ability and impulsivity.…”
Section: Neuropsychological Consequences Of Alcohol Usementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, early age drinkers seem to exhibit a higher susceptibility to the deleterious consequences of alcohol on the brain. Accordingly, several studies in both animals and humans have highlighted the major neurotoxic effects of acute intermittent alcohol consumption in the adolescent brain (10)(11)(12)(13), especially in the late matured structures such as the prefrontal cortex (PFC) (14)(15)(16)(17). In this sense, the youth tendency to engage in BD during adolescence has been associated with a protracted maturing course of the regions comprising this circuitry (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…These statistics are concerning because excessive alcohol use during adolescence is associated with a myriad of negative consequences including alcohol and substance use disorders (AUD, SUD; Dwyer‐Lindgren et al, 2018), and other mental health problems (Pompili et al, 2010; Teesson et al, 2010; Welsh et al, 2017). Alcohol use during adolescence has also been associated with alterations in brain structure and function, including aberrant activation patterns during response inhibition tasks (for review, see Lees et al, 2020; Lees et al, 2019; Squeglia and Cservenka, 2017; Squeglia and Gray, 2016), as well as poorer test performance across cognitive domains, with executive functions and memory being the most vulnerable (Gould, 2010; Lees et al, 2019). Recent longitudinal neuroimaging studies have begun investigating, and have shown, that underlying neural vulnerabilities of response inhibition in substance‐naïve children appear to contribute to earlier initiation and problematic progression of alcohol use during adolescence (Squeglia and Cservenka, 2017).…”
mentioning
confidence: 99%